2019
DOI: 10.1038/s41419-019-1315-9
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin ameliorates lupus autoimmunity by inhibiting differentiation of Tfh cells and inducing expansion of Tfr cells

Abstract: Baicalin is a natural compound isolated from Chinese herb, which has been reported as an anti-inflammatory drug. Here, we demonstrated that Baicalin treatment could reduce urine protein, inhibit anti-ds-DNA antibody titers, and ameliorate lupus nephritis in MRL/lpr lupus-prone mice. Baicalin inhibited Tfh cell differentiation and IL-21 production, but promoted Foxp3+ regulatory T cell differentiation including part of follicular regulatory T (Tfr) cells. Intravenous injection of Baicalin-induced Foxp3+ regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…MRL/lpr mice spontaneously develop a severe lupus-like disease that shares several of the immunologic and clinical manifestations of human lupus [31]. Several studies have shown that T FH cells are expanded in the spleens of MRL/lpr mice [32,33]. R848 is an immune-response modi er that activates immune cells through Toll-like receptors (TLRs) 7 and 8 [34].…”
Section: Discussionmentioning
confidence: 99%
“…MRL/lpr mice spontaneously develop a severe lupus-like disease that shares several of the immunologic and clinical manifestations of human lupus [31]. Several studies have shown that T FH cells are expanded in the spleens of MRL/lpr mice [32,33]. R848 is an immune-response modi er that activates immune cells through Toll-like receptors (TLRs) 7 and 8 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneally injected allā€trans retinoic acid in EAMG rats and caspaseā€1 inhibitor in mice have ameliorated disease severity concomitant with an increased frequency of Tfr cells and decreased frequency of Tfh cells . Baicalin treatment has also been found to ameliorate lupus nephritis in MRL/lpr lupusā€prone mice by enhancing the expansion of Tfr cells and suppressing the differentiation of Tfh cells . Methods to enhance Treg cells numerically and functionally have been under clinical trials in AIDs, so we wonder whether Tfr cells can be applied for therapeutic interventions in AIDs, infections, cancers, allergies and other disorders.…”
Section: Challenges and Unsolved Questions Of Tfr Cellsmentioning
confidence: 99%
“…110,111 Baicalin treatment has also been found to ameliorate lupus nephritis in MRL/lpr lupus-prone mice by enhancing the expansion of Tfr cells and suppressing the differentiation of Tfh cells. 112 Methods to enhance Treg cells numerically and functionally have been under clinical trials in AIDs, 109 so we wonder whether Tfr cells can be applied for therapeutic interventions in AIDs, infections, cancers, allergies and other disorders. According to their role in inhibiting antibody generation, regulation of Tfr cells may strengthen the efficacy of vaccines.…”
Section: Challenges and Unsolved Questions Of Tfr Cellsmentioning
confidence: 99%
“…HepG2 (HB-8065) cells were purchased from ACTT and maintained at 37Ā°C in DMEM containing 10% FBS in a 5% CO 2 atmosphere. Cells were pretreated with 50 Ī¼M chloroquine (Sigma) or 1 Ī¼M MHY1485 (Med Chem Express), which is a mTOR agonist [23]. Cells were treated with 125 mM oleate for 24 h; then, medium were changed by supplement with 10 nM exendin-4 (Sigma) to maintain the fatty acids stress for 24 h. After that, HepG2 cells were cultured without exendin-4 for an additional 24 h. After treatment with exendin-4 and oleate or oleate alone for 24 h, cells were harvested.…”
Section: Cells and Cellmentioning
confidence: 99%